Bilateral Congenital Colobomas and Vitiligo in a Blind Middle Aged Female - Tariq Khurram; Farhangi Arezo; Rana Fauzia (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2014)
Bilateral Congenital Colobomas leading to blindness in this middle aged female.